Reliability of digital radiographs in measuring the vertical and horizontal dental implants’ dimensions a retrospective study - Rakan Shaheen, Dr.; Muna Binladin, Dr.; Alanoud Bin Muammar, Dr.; Shuaa Alonazi, Dr.; Amjad Alharbi, Dr.; Bader Bamousa, Dr.; Ahmed Alahmari, Dr. (International Journal of Dental Research, 2019)
Introduction: Digital radiography can take accurate measurements. In implant dentistry, intraoral periapical (PA), bite-wing (BW) and panoramic (OPG) radiographs are being used, although it had limitations of distortion. This research aims to assess the accuracy of digital radiography in measuring dental implants and to evaluate the SIDEXIS software’s reliability in measuring their dimensions.Materials and Methods: Over 192 implants from 316 radiographs were selected. All radiographs were analyzed using SIDEXIS software. Statistical analysis was performed using SPSS.Results: Statistically significant differences (P < 0.5) between the actual heights and widths compared to the measured radiographic dimensions. Over all the distortion was greatest in OPGs. The magnifications were 2.48mm in height and 0.82mm in width for OPGS, 0.17mm in width for BWs while in PAs it was 1.37mm in height and 0.156mm in width. The magnification was more in maxilla for PAs and OPGs. Anteriorly the PAs had the greatest magnification (2.16mm), and OPGs had the greatest at (3.03mm) in height posteriorly.Conclusion: Digital OPG, PA and Bitewing radiographs are reliable for performing dimensions linear measurements for implants, and PAs have the highest precision. Additionally, SIDEXIS software provided accurate results and can be considered a reliable method for implants’ assessment.